Social Media Literacy of Tourism Village Activists in Wanurejo, Borobudur: Does Age Matter? - Sari, Yoana Puspita; Pambuko, Zulfikar Bagus; Muliawanti, Lintang; Fidian, Athia (CHANNEL: Jurnal Komunikasi, 2022)
Borobudur Temple is one of the five Indonesian super-priority destinations targeted to be the "New Bali." Wanurejo tourist village is one of the areas affected by this and is considered a buffer zone to develop. Therefore, skilled human resources are required in the use of digital technology, especially social media, to be able to promote tourism destinations extensively and to increase tourism visits. This study compared and analyzed Wanurejo tourism village activists' social media literacy levels based on socioeconomic circumstances, particularly age. In order to acquire the data, a questionnaire was used as a data collection instrument. The 87 respondents who were Wanurejo tourism village activists make up the sample for this study. Data analyses were performed using descriptive and differences analysis. The findings demonstrated that the most popular social media platforms for communication, promotion, and information retrieval were WhatsApp, Instagram, and Facebook. Additionally, Wanurejo tourism village activists had moderate social media literacy (71.58), characterized mainly by technical mastery. Based on the characteristics of the respondents, younger tourism village activists had a better level of social media literacy than older ones. According to the latest education, a higher education level was associated with greater social media literacy. As for the aspect of gender, income, and work experience, there were no notable differences in social media literacy. Therefore, strengthening social media literacy to support tourism promotion needs to be focused on millennials and highly educated tourism village activists.